Changing Services for Changing Clients (Columbia University Press, 1969)
A collection of essays on social changes and their effect on people, the social services, and the delivery of these services. Specifically focuses on the demand for social service, concepts of social work treatment and prevention of problems on a community level, concepts of social work treatment of the multiproblem client, and other topics